K. Vaishali K. Vaishali, Homeless: Growing up Lesbian and Dyslexic in India. Hyderabad: Yoda Press. 2023. ISBN 978-93-92099-51-9. - Sarkar, Dwitiya; Dhiman Roy (SARE: Southeast Asian Review of English, 2024)
What does it mean to be dyslexic and lesbian at the same time in a dysfunctional, unsupportive family in India? How does one confront both ableism and homophobia in a complex heteronormative society that always dismisses any “unconventional” traits and behaviors as deviant? Indian-born author and LGBTQ activist K. Vaishali’s narrative reveals the dark, cruel, and repressive side of society by delving deeply into these issues, without worrying about adhering to political correctness. Using life-narrative as a tool, she exposes several myths, misconceptions, and also limitations of knowledge about children with dyslexia. When people in India talk about dyslexia, she says, the image of the stereotyped child from the 2007 highly acclaimed Bollywood film Taare Zameen Par pops into their heads, since what little we know about dyslexia comes from this one cult classic, which indicates our limited understanding of the phenomenon. Moreover, she reveals how she was kicked out of her own house due to her “unnatural” sexual preference from her own home: “I told my mother about my sexuality and from a wicked curse I lost the house, job, and girlfriend- I lost my Bombay life. Since then, I’ve been living out of my suitcase, like I am a fugitive on the run” (Vaishali 5).